Epidemiological and Clinical Features of Three Clustered Cases Co‐Infected with Lyme Disease and Rickettsioses. (31st December 2012) - Xuefei, D.; Qin, H.; Xiaodi, G.; Zhen, G.; Wei, L.; Xuexia, H.; Jiazhen, G.; Xiuping, F.; Meimei, T.; Jingshan, Z.; Yunru, L.; Xiaoling, F.; et al.
Summary Lyme disease and rickettsioses are two common diseases in China. However, the concomitant occurrence of both diseases in a single individual has been reported infrequently in literature. We reported three related female patients admitted at Beijing Ditan Hospital from October to December 2010. They had similar epidemiological histories. At the beginning, they only got a single diagnosis, respectively, but after specific screenings, the final diagnoses were made. Because arthropods can harbour more than one disease‐causing agent, patients can be infected with more than one pathogen at the same time, so the possibility of co‐infection could be higher than what was thought previously. These observations suggested that clinicians should enhance the complete screening of arthropod‐related infectious diseases so as to make an accurate diagnosis and to avoid diagnostic errors.